1981
DOI: 10.1099/0022-1317-55-1-87
|View full text |Cite
|
Sign up to set email alerts
|

The Inhibition of Vaccinia Virus Replication by 5,6-Dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB): an Effect at the Assembly Stage

Abstract: SUMMARYThe step sensitive to DRB (5,6-dichloro-l-fl-D-ribofuranosylbenzimidazole) in vaccinia virus replication has been investigated. Ninety gM-DRB extensively inhibited the yield of vaccinia virus after infection of Ehrlich ascites tumour cells. DRB did not inhibit cytoplasmic vaccinia DNA replication. Cytoplasmic viral RNA synthesis (both early and late) was also apparently unaffected and the virus RNAs thus synthesized were normal sized. The expression of early, intermediate and late proteins was not detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1984
1984
1998
1998

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…19 Previous reports of l-/?-D-ribofuranosylbenzimidazole nucleosides29-31 indicate that the Jy.%' coupling constants tend to be >5 Hz for such compounds and therefore cannot be used to establish anomeric configuration. We found that all nucleosides (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) prepared in this study possessed a Jy.% >5 Hz. However, the dethiation of 5 to give DRB (with a Jy.y of 6.3 Hz) established the /3-anomeric configuration for all nucleosides (4-23).…”
Section: Introductionmentioning
confidence: 60%
“…19 Previous reports of l-/?-D-ribofuranosylbenzimidazole nucleosides29-31 indicate that the Jy.%' coupling constants tend to be >5 Hz for such compounds and therefore cannot be used to establish anomeric configuration. We found that all nucleosides (4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23) prepared in this study possessed a Jy.% >5 Hz. However, the dethiation of 5 to give DRB (with a Jy.y of 6.3 Hz) established the /3-anomeric configuration for all nucleosides (4-23).…”
Section: Introductionmentioning
confidence: 60%
“…Third, a kinase, which must be an early protein, leads within the early period to a complete phosphorylation of S2. At the stage in infection (60 min in our experimental system) the early viral mRNAs are preferentially translated [40]. The phosphorylation of S13 thus begins, and also depends on an early vaccinia synthesis [3] (and discussed above).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, ORB markedly inhibits the multiplication of vaccinia virus Tamm and Overman, 1957;Bucknall, 1967). However, ORB does not inhibit cytoplasmic vaccinia gene expression, but it impairs viral DNA encapsidation (Pothier et al, 1981). In addition to its in vitro antiviral effects (Sehgal and Tamm, 1980), ORB has been shown to suppress the replication of influenza virus in embryonic chicken eggs and in mice (Tamm et aI., 1954).…”
Section: Introductionmentioning
confidence: 99%